Depression, anxiety and cardiovascular disease: Which symptoms are associated with increased risk in community dwelling older adults? - KENNY, ROSE ANNE; O'REGAN, CLAIRE; LAWLOR, BRIAN; SAVVA, GEORGE; CRONIN, HILARY (My University, 2012)
Depression is a risk factor for Cardiovascular Disease (CVD). It has been reported that somatic symptoms of depression and not cognitive symptoms are associated with increased risk although findings have been inconsistent. Few studies have examined whether co-morbid anxiety confers additive risk. METHODS: We conducted a cross sectional analysis of 7872 community dwelling adults aged 50 years and over from The Irish LongituDinal Study on Ageing (TILDA). Depressive and anxiety symptoms were assessed with Center for Epidemiologic Studies Depression (CES-D) scale and the anxiety subscale of the Hospital Anxiety and Depression Scale (HADS-A), respectively. We conducted logistic regression analyses to determine the relationship between depression, anxiety, individual depressive symptoms and CVD. We further determined whether co-morbid anxiety was associated with increased risk. RESULTS: Seven hundred and thirty eight (9.4%) study participants reported clinically significant depression. Depression was associated with 80% increased risk of CVD following adjustment for cardiovascular risk factors. Individual depressive symptoms most consistently associated with CVD included low mood, sadness, amotivation, fatigue, diminished appetite and concentration difficulties. Anxiety was associated with increased risk of CVD but did not confer additive risk in participants with depression. LIMITATIONS: Cross sectional design. CONCLUSION: Core symptoms of depression, which are both cognitive and somatic in nature, are associated with increased risk of CVD while co-morbid anxiety did not confer additive risk. It is important that clinicians give due regard both to both cognitive and somatic symptoms of depression when determining cardiovascular risk. Future longitudinal investigation should confirm these findings and explore potential pathological mechanisms.
PUBLISHED
PMID: 22858218
Keywords: cardiovascular risk; cardiovascular risk